Financial capital, constraints, partners, and performance: An empirical analysis of Indonesia SMEs - I Wayan Widnyana; I Made Dauh Wijana; Almuntasir Almuntasir (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2021)
Indonesia's small and medium enterprises (SMEs) are considered the backbone of the national economy. However, the fact that SMEs still contribute less to the national gross domestic product (GDP) in terms of value-added, need to be addressed. While previous studies mainly focused on financial (access) constraints as one of the major constraints faced by small enterprises which affect their growth and performances, this study aims to extend the relationship between capital and financial performance of Indonesia SMEs with the moderating effect of financial constraints and partners. This study is different from others as it uses a bigger panel dataset which is about 4.36 million SMEs in Indonesia and is the first to explore the role of financial partners comprehensively. Moreover, the panel regression model with geographic analysis unit uses as a data analysis method. The results of the study show that financial capital has a positive and significant effect on the financial performance of SMEs. Furthermore, while the moderation role of financial partners on the relationship between financial capital and financial performance of Indonesia SMEs was failed to prove, the negative moderation effect of financial constraints was able to prove in this study.